Correlation between hematological indicators in acclimatized high-altitude individuals and acute mountain sickness - Zhicai Li; Jun Xiao; Cuiying Li; Xiaowei Li; Daoju Ren (PeerJ)
Background The impact of acute mountain sickness (AMS) on individuals ascending to plateaus, soon after exposure to high altitudes, is well-documented. However, the specific relationship between AMS and alterations in blood parameters remains unclear. Methods A total of 40 healthy volunteers were recruited. Following their arrival at an altitude of 3,300 m, an AMS questionnaire survey was administered 48 h later. Based on the AMS scores obtained, participants were categorized into three groups: non-AMS, mild AMS, and moderate/severe AMS (encompassing both moderate and severe cases). Blood routine tests were performed on all groups at 3-, 7-, and 30-days post-arrival at the plateau, with blood oxygen saturation tests conducted at 3 and 30 days after rapidly entering the plateau. Results In the current investigation, a total of 40 participants were stratified into non-AMS (n = 24), mild-AMS (n = 8), and moderate/severe-AMS (n = 8) cohorts subsequent to rapid ascension to an altitude of 3,300 m. The incidence of AMS in this study was 40%. Noteworthy elevations in red blood cells (RBC), hemoglobin (Hb), and hematocrit (HCT) levels were noted at the 3-day mark post-ascent across all delineated groups. By the 7th day, the moderate/severe-AMS cohort displayed sustained increments in Hb and HCT levels, whereas solely HCT levels rose in the mild-AMS and non-AMS cohorts. Upon reaching the 30-day milestone, the moderate/severe-AMS group demonstrated a reduction in RBC, Hb, and HCT levels, while only HCT levels decreased in the mild-AMS and non-AMS groups. Furthermore, it was observed that all groups exhibited notable reductions in oxygen saturation (SpO2) at 3 days post-ascent, followed by a partial recovery at 30 days, albeit remaining below baseline levels. The correlation analysis results indicated that RBC, Hb, and HCT exhibited a positive correlation with the severity of AMS after a 7-day acclimatization period at high altitude. Conversely, SpO2 demonstrated a negative correlation with the severity of AMS following the same duration at high altitude. The findings of the study suggest a strong association between alterations in RBC, Hb, and HCT levels and AMS, particularly among individuals in the moderate/severe-AMS category who displayed more significant fluctuations in these parameters. Conclusion Individuals suffering from moderate to severe AMS demonstrated increased levels of RBC, Hb, and HCT, as well as reduced SpO2, indicating a greater need for oxygen adaptation to high-altitude hypoxia. These findings emphasize the physiological adjustments to high altitudes and their potential implications for the treatment of AMS.